Factors that influence trust in the police in Mexico - Baek, Hyunin (International journal of comparative and applied criminal justice, 2022)
Despite Mexico’s justice reform, most Mexican citizens do not trust in their criminal justice system. Particularly, public dissatisfaction with the police has not been solved in Mexico. Researchers have examined citizens’ trust in the police to improve public-police relationship in Mexico. Relatively less attention, however, has been made to the theoretical framework, which explores factors such as instrumental and expressive factors that influence the public trust in the police. Thus, using a data set from the Latin American Public Opinion Project, this study conducted multiple regressions to find those factors. Results indicated that neighbourhood security (key instrumental factors) was significantly related to trust in the police. In addition, police corruption showed a negative association with trust in police and public satisfaction with police performance. This study found supporting evidence that securing neighbourhoods builds more confidence in the police among residents. Overall, these results suggest meaningful strategies to improve trust in the Mexico’s police.